Implementation of Religious Moderation Education in the Islamic Education Curriculum Based on Local Wisdom through the Learning Management System (LMS) in Higher Education - Su’udin Aziz; Pramesti Wulandari (LPPM Undiksha, 2026)
Religious moderation education in higher education faces various ongoing challenges, including predominantly normative learning approaches, limited contextualization, and the suboptimal integration of digital technology and local wisdom. This study aims to develop and test the effectiveness of religious moderation education within the Islamic Religious Education (PAI) curriculum based on the local wisdom of Wayang Thengul through the utilization of a Learning Management System (LMS). The research employed a Research and Development (R&D) approach using the ADDIE model. The research subjects consisted of 30 PAI students. Data were collected through pre-test and post-test assessments, student perception questionnaires, observations of LMS-based learning activities, and expert validation. Data analysis was conducted using descriptive statistics and a paired sample t-test. The results indicated a significant improvement in students’ understanding of religious moderation, as evidenced by higher post-test mean scores compared to pre-test scores. Furthermore, LMS-based learning was shown to enhance students’ participation and contextual reflection. The study concludes that the integration of Wayang Thengul local wisdom into the PAI curriculum through an LMS represents an effective and adaptive learning model for strengthening religious moderation in higher education in the digital era. These findings provide practical contributions to the development of culturally and digitally based PAI curricula and serve as a reference for higher education institutions in designing contextual, inclusive, and sustainable religious moderation learning.